Application of vac in type III open fractures - Atiç, Ramazan; Alemdar, Celil; Azboy, İbrahim; Bulut, Mehmet; Çaçan, Mehmet Akif; Gem, Mehmet (Derman Medical Publishing, 2018)
Aim: Functional results of patients with Type III open long bone fractures treated with vacuum-assisted closure (VAC) and approximating sutures were evaluated. Material and Method: A total of 21 patients (4 female, 17 male with a mean age of 27 years, range: 3-64 years) with Gustilo-Andersen Type 3 open fracture were included in the study. The mean follow-up period was 25.67 months (range, 9-52 months). Thirteen patients had Type IIIB and eight patients had Type IIIC open fractures. Following a large debridement and irrigation in an operating room setting, wound dimensions were measured. Subsequently, VAC was applied. During the application, skin traction sutures were applied over the vacuum sponge. During the last dressing change in which a dean granulation tissue was obtained, the wound was closed following the measurement of its dimensions. Wound dimensions measured during the large debridement in the operating room were compared with the wound dimensions measured after the final VAC application. Results: Mean duration between trauma and operation was 7.57 hours (range, 2-23 hours). The wound was closed with delayed primary suturing in seven patients. In the remaining 14 patients, wound dimensions measured following the last VAC application were found to be decreased with a mean of 40.02% (range, 20-60%). Seven patients underwent a skin graft, two had a free flap application, four had a fasciocutaneous flap, and one had a fasciocutaneous flap + graft application. Two patients underwent revision operations for graft failure. Five patients (23.8%) developed a deep wound infection. The infections resulted in osteomyelitis in two patients (9.5%). Discussion; VAC application together with skin traction sutures in Type IIIB and C open fractures decreases wound size dimension of a graft or flap to be applied. Also it may reduce the requirement for secondary interventions.
WOS: 000445434700007
Keywords: Open Fracture; Vacuum-Assisted Closure; Skin Traction Suture; Wound Closure